Treatment of corruption and strengthening integrity in Kosovo Police - Maliqi, Reshat; Maloku, Elda (Technium Social Sciences Journal, 2021)
The object of the research in the paper is the treatment of corruption and strengthening the integrity of the Kosovo Police. The aim of the conducted research is not only to inform the public and the reader to understand the causes and the specific forms of corrupted behavior and abuse of official duty from the police officers, but to also inform them with damages that are caused to the values of police culture and ethics in general, as well as the measures to be taken. Growth and development of the Police with human resources and legal competencies, by a certain individual is often accompanied by abuse and deviation from the exercise of those powers during the exercise of official duty, and investigations conducted during 2015-2019 testify the involvement of police officers in criminal offenses with corrupt elements. This research is based on and implements a research and comparative approach and model related to the phenomenon of corruption in the Kosovo police for the period from 2015-2019. The case that is being studied aims to learn through the comparative method regarding the investigation and treatment of corruption in the police of Kosovo and Albania. In the final analysis of this paper from all the conclusions and recommendations it can be said that the ways of recognizing the existence of corrupt behaviors and identifying work in preventing, detecting and cracking down on this negative phenomenon by both the police themselves and the specialized oversight and control structures, avoids and reduces corruption.